High-barrier multilayer co-extrusion biodegradable film with transparency and heat shrinkage and preparation method thereof
Patent Information
- Application Number
- CN202610828561.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-09
- Publication Date
- 2026-08-28
AI Technical Summary
然而,现有单层生物降解薄膜普遍存在三大技术瓶颈:(1)阻隔性能差:PBAT薄膜的氧气透过率通常高于800 cm³/(m²·24h·atm),远低于传统高阻隔材料;PLA薄膜韧性差;PPC热稳定性差;PVA耐水性差
(1)双重阻隔且宽范围可调:创新引入纳米VCI阻隔剂,与层状纳米填料形成协同阻隔,通过调整配方与拉伸工艺,可实现气体宽范围连续可调,满足从超高阻隔到适度透气的多样化需求。
Smart Images

Figure CN122645701A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of packaging materials technology, specifically to a high-barrier multilayer co-extruded biodegradable film that combines transparency and heat shrinkage, and its preparation method. In particular, it relates to a fully biodegradable film that incorporates a nano-VCI barrier agent and a special heat-sealing layer, and simultaneously possesses high transparency, adjustable heat shrinkage, and a wide range of barrier properties, and its preparation method. Background Technology
[0002] With the advancement of global plastic ban policies and the enhancement of environmental awareness, biodegradable plastics such as polylactic acid (PLA), polybutylene adipate terephthalate (PBAT), polypropylene carbonate (PPC), and polyvinyl alcohol (PVA) have gradually become important alternatives to disposable packaging materials. However, existing single-layer biodegradable films generally suffer from three major technical bottlenecks: (1) Poor barrier performance: The oxygen permeability of PBAT film is usually higher than 800 cm³ / (m²·24h·atm), which is far lower than that of traditional high barrier materials; PLA film has poor toughness; PPC has poor thermal stability; and PVA has poor water resistance. A single material is difficult to meet the diverse barrier requirements of different packaging. (2) Insufficient transparency: Especially PBAT-based films, due to their crystallization characteristics and compatibility with fillers, have high haze and low light transmittance, making them unsuitable for packaging that requires transparent windows, such as cigarette packaging, gift packaging, and transparent bags. In existing technologies, although adding nanofillers can improve barrier performance, it often comes at the cost of sacrificing transparency. (3) Poor heat shrinkage: Biodegradable materials generally lack heat shrinkage properties or have extremely low heat shrinkage rates, making them difficult to apply to applications such as heat shrink labels and bulk packaging that require close adhesion to irregularly shaped objects. Traditional heat shrink films mostly use non-degradable materials such as PVC, PETG, and POF, and the development of biodegradable heat shrink films is a technological gap in this field.
[0003] In addition, existing biodegradable films also have obvious defects in heat-sealing performance: (1) the heat-sealing temperature window is narrow, usually only 10~15℃, which requires high temperature control accuracy of packaging equipment; (2) the heat-sealing performance against contamination is poor, and the heat-sealing strength drops sharply when packaging oily or powdery foods; (3) the compatibility between the heat-sealing layer and the barrier layer is poor, and it is easy to delaminate during multilayer co-extrusion. At the same time, the traditional high barrier strategy mainly relies on the passive barrier of the "tortuous path" of layered nanofillers, which lacks the function of active adsorption or chemical binding of small molecule gases, and the barrier efficiency needs to be further improved. Therefore, developing a biodegradable high barrier film with both passive barrier and active adsorption mechanisms and excellent heat-sealing performance has significant technological progress significance. Summary of the Invention
[0004] The purpose of this invention is to overcome the shortcomings of the aforementioned background technology and provide a high-barrier multilayer co-extruded biodegradable film that combines transparency and heat shrinkage, as well as its preparation method. This invention achieves active barrier properties by introducing a nano-VCI barrier agent (vapor phase corrosion inhibitor / adsorption nanomaterial), and achieves wide-window, contamination-resistant heat sealing through a dedicated heat-sealing layer design. Combined with organic-inorganic hybridization, alloying, multilayer co-extrusion, and biaxial stretching technologies, it comprehensively overcomes the performance bottlenecks of existing biodegradable films.
[0005] To achieve the objectives of this invention, the high-barrier multilayer co-extruded biodegradable film of this invention, which combines transparency and heat shrinkage, comprises a heat-sealing layer, a first barrier core layer, a second barrier core layer, and an outer surface layer; wherein, the heat-sealing layer is a low-melting-point biodegradable polyester layer, selected from one or more of polybutylene adipate terephthalate (PBAT), polybutylene succinate (PBS), and polycaprolactone (PCL); the first barrier core layer and the second barrier core layer are each independently selected from one or more of polyvinyl alcohol (PVA), polypropylene carbonate (PPC), polylactic acid (PLA), and PBAT, and contain organic-inorganic hybrid nanofillers and nano-VCI barrier agents; the outer surface layer is a heat-resistant, anti-adhesion biodegradable layer, selected from one or more of PLA, PVA, or PLA / PHA.
[0006] Furthermore, in some embodiments of the present invention, the heat-sealing layer further contains an anti-fouling heat-sealing agent, which is polyethylene oxide (PEO), polycaprolactone-polyethylene glycol (PCL-PEG) block copolymer, or fatty acid amide.
[0007] Furthermore, in some embodiments of the present invention, the amount of the anti-fouling heat-sealing agent added is 0.1% to 2% of the mass of the heat-sealing layer, so that the heat-sealing layer can still maintain its heat-sealing strength in the presence of oil or powder. The melting point of the heat-sealing layer should be 20 to 60°C lower than that of the core layer and the outer layer to ensure that it does not affect other layers during heat sealing.
[0008] Furthermore, in some embodiments of the present invention, the organic-inorganic hybrid nanofiller is one or more of nano-montmorillonite, nano-silica, and nano-kaolinite.
[0009] Furthermore, in some embodiments of the present invention, the organic-inorganic hybrid nanofiller is pretreated with a silane coupling agent (KH550 or KH570); preferably, the surface pretreatment method is to mix at 95-105°C for 10-20 min.
[0010] Furthermore, in some embodiments of the present invention, the particle size of the organic-inorganic hybrid nanofiller is 30~500 nm.
[0011] Furthermore, in some embodiments of the present invention, the amount of the organic-inorganic hybrid nanofiller added is 1% to 15% of the total mass of the film.
[0012] The nano-VCI barrier agent described in this invention is a class of functional materials with nanoscale properties capable of actively adsorbing or chemically binding small molecule gases (O2, H2O, CO2, corrosive gases). Specifically, it is selected from one or more of the following: nano-zeolites (pore size 0.3~1 nm, capable of selectively adsorbing O2 and H2O), nano-metal-organic framework materials (MOFs, such as ZIF-8 and MIL-101, which have ultra-high specific surface area and gas affinity), nano-activated carbon, and nano-molecular sieves (such as 4A, 5A, and 13X).
[0013] Furthermore, in some embodiments of the present invention, the nano-VCI barrier agent is pre-modified with a hydrophilic surface. The modifier is selected from silane coupling agents, titanate coupling agents, or oleic acid. After modification, the contact angle of the powder changes from hydrophilic (<20°) to hydrophobic (60~90°) to improve compatibility with the polyester matrix. After surface hydrophilic modification, these nanoparticles are uniformly dispersed in the polymer matrix, which not only prolongs the gas diffusion path but also fixes gas molecules through adsorption or chemical bonding, significantly improving the barrier efficiency.
[0014] Furthermore, in some embodiments of the present invention, the particle size of the VCI barrier is 20~200 nm.
[0015] Furthermore, in some embodiments of the present invention, the amount of the VCI barrier agent added is 0.5% to 10% of the total mass of the film, preferably 1% to 5%.
[0016] Furthermore, in some embodiments of the present invention, the total thickness of the film is 20-200 μm, wherein the heat-sealing layer thickness accounts for 10%-25%, the total thickness of the first barrier core layer and the second barrier core layer accounts for 50%-70%, and the outer surface layer thickness accounts for 15%-30%.
[0017] Furthermore, in some embodiments of the present invention, the first barrier core layer is the main barrier layer, with a thickness accounting for 25% to 40% of the total film thickness. It adopts a high barrier resin, such as PVA / PLA, PPC / PLA, etc., and adds organic-inorganic hybrid nanofillers (such as 5% to 15% nano montmorillonite) and nano VCI barrier agents (0.5% to 5% nano zeolite) to form a double barrier.
[0018] Furthermore, in some embodiments of the present invention, the second barrier core layer is an auxiliary barrier layer with a thickness of 25% to 40% of the total film thickness. It can be made of PBAT / PLA resin with good flexibility, with the addition of nano-silica and nano-VCI barrier agents, thus taking into account both barrier and mechanical properties.
[0019] Furthermore, in some embodiments of the present invention, the thickness of the heat-sealing layer is 5~30 μm.
[0020] Furthermore, in some embodiments of the present invention, the outer surface layer may be without or with a small amount of anti-blocking agent (such as 0.1% to 0.5% nano-silica).
[0021] Furthermore, in some embodiments of the present invention, the film has a light transmittance of ≥85% in the visible light region and a haze of ≤8%; a heat shrinkage rate of 5%~60% under conditions of 80°C and 10 min; and a heat sealing strength of ≥12N / 15mm and a heat sealing window width of ≥30°C in the range of 80~140°C.
[0022] Furthermore, in some embodiments of the present invention, the film can be adjusted by regulating the type and ratio of resin, the type and content of nanofillers, the number of layers, the layer thickness ratio, and the stretching ratio, so that the water vapor transmission rate of the film is adjustable in the range of 20~2000 g / (m²·day), the oxygen transmission rate is adjustable in the range of 2~5000 cm³ / (m²·day·atm), and the carbon dioxide transmission rate is adjustable in the range of 5~20000 cm³ / (m²·day·atm).
[0023] Furthermore, the present invention also provides a method for preparing the aforementioned high-barrier multilayer co-extruded biodegradable film that combines transparency and heat shrinkage, the method comprising the following steps: (1) Raw material pretreatment: each layer of resin is dried, and the nanofiller and nano VCI barrier are respectively pretreated by coupling agent surface treatment; (2) Multi-layer co-extrusion blow molding: The materials of each layer are premixed according to the formula and fed into the extruder of the multi-layer co-extrusion blow molding unit. The materials of each layer are plasticized and melted at 150~230℃ and then extruded through a multi-layer die head (170~210℃) to form a molten preform. (3) Inflate the preform (inflation ratio 2~6), cool it, and draw it (drawing ratio 2~8) to form a primary film; (4) Biaxial stretching: After the blown film bubble is cooled, it is reheated to the stretching temperature (40~100℃) and stretched longitudinally (2~8 times) and transversely (2~8 times). Then it is heat-treated in the heat setting zone (50~120℃) and finally wound up. The thermal shrinkage rate and transparency of the film are adjusted by controlling the stretching ratio, stretching temperature and heat setting temperature of the biaxial stretching; the heat sealing performance is adjusted by selecting heat sealing layer materials with different melting points and adding anti-fouling additives.
[0024] Furthermore, in some embodiments of the present invention, the film is heat-sealed at a temperature of 80~120°C, a pressure of 0.2~0.5MPa, and a time of 0.5~2 seconds, with a heat-sealing strength ≥12 N / 15mm, and no stringing or sticking to the roller at the heat-sealed area.
[0025] Furthermore, in some embodiments of the present invention, the multilayer co-extrusion blow molding employs a five-layer co-extrusion blow molding unit (corresponding to a symmetrical structure of heat-sealing layer / first core layer / second core layer / outer layer / second core layer / first core layer / heat-sealing layer, or an asymmetrical four-layer structure).
[0026] Furthermore, in some embodiments of the present invention, the extrusion temperatures of each layer are as follows: Heat seal temperature: 150~170℃ (low melting point), core layer: 180~210℃, outer layer: 190~220℃. Die head temperature: 190℃.
[0027] Furthermore, in some embodiments of the present invention, the melting point of the heat-sealing layer material is 20-60°C lower than that of the outer layer and core layer materials, and the heat-sealing initiation temperature is 80-100°C.
[0028] Furthermore, in some embodiments of the present invention, after biaxial stretching, the crystallinity of the heat-sealing layer is controlled at 15% to 35% to obtain a wide heat-sealing window.
[0029] Furthermore, in some embodiments of the present invention, the heat setting temperature should be 10-20°C lower than the melting point of the heat seal layer to obtain a rapid heat seal response.
[0030] In another aspect, the present invention also provides a heat-shrinkable packaging bag or a food preservation packaging bag, wherein the heat-shrinkable packaging bag or food preservation packaging bag is made by heat-sealing or heat-shrink molding of the aforementioned high-barrier multilayer co-extruded biodegradable film that combines transparency and heat shrinkability.
[0031] Compared with the prior art, the advantages of the present invention are as follows: (1) Dual barrier and wide range adjustable: The innovative introduction of nano VCI barrier agent forms a synergistic barrier with layered nano filler. By adjusting the formula and stretching process, the gas can be continuously adjusted in a wide range to meet the diverse needs from ultra-high barrier to moderate permeability.
[0032] (2) Breakthrough in high transparency and adjustable heat shrinkage: The use of nanofillers with particle size <100 nm and refractive index matching, combined with biaxial stretching orientation, solves the common problem of opacity of PBAT-based films; by controlling the stretching ratio and heat setting temperature, the heat shrinkage rate can be arbitrarily adjusted within the range of 5%~60%, filling the technical gap of fully biodegradable heat shrink film.
[0033] (3) Excellent heat-sealing and mechanical properties: A low-melting-point special heat-sealing layer is designed and anti-pollution additives are added to achieve a heat-sealing window of ≥30℃, low-temperature heat sealing, and oil-resistant heat-sealing strength retention rate of ≥70%; the comprehensive mechanical properties are superior to existing single-layer biodegradable films, meeting the requirements of automated packaging and heavy-duty packaging. All components are compostable and biodegradable, with a composting degradation rate (60 days) of ≥90%, making it environmentally friendly. Attached Figure Description
[0034] Figure 1 This is a flowchart of the thin film preparation process of the present invention. Detailed Implementation
[0035] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. Additional aspects and advantages of this invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. It should be understood that the following description is merely illustrative and not intended to limit the invention.
[0036] The terms “comprising,” “including,” “having,” “containing,” or any other variations thereof, as used herein, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus that includes the listed elements is not necessarily limited to those elements, but may include other elements not expressly listed or elements inherent to such composition, step, method, article, or apparatus.
[0037] The conjunction "composed of..." excludes any unspecified elements, steps, or components. If used in a claim, this phrase makes the claim closed, excluding materials other than those described, except for associated conventional impurities. When the phrase "composed of..." appears in a clause of the body of a claim rather than immediately following it, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0038] When a quantity, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pair of any upper or preferred value with any lower or preferred value, regardless of whether the range is disclosed individually. For example, when the range “1 to 5” is disclosed, the described range should be interpreted as including the ranges “1 to 4”, “1 to 3”, “1 to 2”, “1 to 2 and 4 to 5”, “1 to 3 and 5”, etc. When numerical ranges are described herein, unless otherwise stated, the range is intended to include its endpoints and all integers and fractions within that range.
[0039] The singular form includes the plural objects of discussion unless the context clearly indicates otherwise. "Optional" or "any one" means that the matter or event described thereafter may or may not occur, and the description includes both the possibility that the event occurs and the possibility that the event does not occur.
[0040] Approximate terms used in the specification and claims to modify quantities indicate that the invention is not limited to that specific quantity, but also includes acceptable modifications close to that quantity that do not alter the relevant essential function. Correspondingly, the use of "about," "approximately," etc., to modify a numerical value means that the invention is not limited to that precise value. In some instances, approximate terms may correspond to the precision of the instrument used to measure the value. In this application's specification and claims, scope definitions can be combined and / or interchanged, unless otherwise stated, these scopes include all subscopes contained therein.
[0041] The indefinite articles “a” and “an” preceding an element or component of this invention do not impose any limitation on the quantity (i.e., number of times) of the element or component. Therefore, “an” or “a” should be interpreted as including one or at least one, and the singular form of an element or component also includes the plural form, unless the quantity clearly refers only to the singular form.
[0042] Furthermore, the terms "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., described below refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms are not necessarily directed at the same embodiment or example. Moreover, the technical features involved in the various embodiments of the present invention can be combined with each other as long as they do not conflict with each other. Example 1 (including nano-VCI and heat sealing)
[0043] Structure: Four-layer asymmetric structure (heat-sealing layer / first core layer / second core layer / outer layer) Heat seal layer: PBAT (melting point 125℃) + 1% PEO (antifouling additive), thickness 10μm.
[0044] First core layer: PVA / PLA=60 / 40 + 8% nano-montmorillonite + 3% nano-zeolite (ZSM-5, particle size 80nm, modified with oleic acid), thickness 25μm.
[0045] Second core layer: PBAT / PLA=70 / 30 + 5% nano silica + 2% nano MOF (ZIF-8, particle size 150nm), thickness 25μm.
[0046] Outer layer: PLA / PHA=80 / 20, thickness 10μm.
[0047] Process: Five-layer co-extrusion (symmetrical structure of heat-sealing layer / first core layer / second core layer / outer layer / second core layer / first core layer / heat-sealing layer, total of 7 layers, effectively equivalent to four layers of material). Extrusion temperature: heat-sealing layer 160℃, first core layer 195℃, second core layer 190℃, outer layer 200℃. Blow-up ratio 4, draw ratio 5. Biaxial stretching: longitudinal 3.5 times, transverse 3.5 times, stretching temperature 65℃, heat-setting temperature 90℃. Total thickness 70μm.
[0048] performance: Barrier: OTR=28 cm³ / (m²·day·atm), WVTR=25 g / (m²·day), CO2TR=95 cm³ / (m²·day·atm); Transparency: 89% light transmittance, 5% haze; Heat shrinkage (80℃ / 10min): 15% longitudinally, 13% transversely; Heat sealing performance: Heat sealing initiation temperature 90℃, heat sealing strength (110℃, 0.3MPa, 1s) = 14.5 N / 15mm, heat sealing window 90~130℃ (ΔT=40℃); after coating the surface with oil (0.5g / m² soybean oil), the heat sealing strength still reaches 11.2 N / 15mm; MFR = 2.8 g / 10min; Degradation rate: 92%; Compared with Comparative Example 1 (without nano VCI), OTR was reduced by 38% and WVTR was reduced by 22%. Example 2 (Ultra-high barrier PVA / PPC + Nano VCI)
[0049] Structure: Five-layer symmetrical (heat-sealing layer / core layer A / core layer B / outer layer / core layer B / core layer A / heat-sealing layer), heat-sealing layer is PCL (melting point 60℃) + 0.5% oleamide; core layer A: PVA / PPC=70 / 30 + 10% nano montmorillonite + 5% nano MOF (MIL-101); core layer B: PVA / PPC=80 / 20 + 8% nano zeolite; outer layer: PLA.
[0050] Process: Casting-biaxial stretching, stretching temperature 50℃, longitudinal stretch 5 times, transverse stretch 5 times, heat setting temperature 80℃. Thickness 50μm.
[0051] Performance: OTR=1.8, WVTR=18, CO2TR=6; light transmittance 91%, haze 3%; heat shrinkage rate 48%; heat seal strength (80℃, 0.3MPa, 1s) = 13.2 N / 15mm, heat seal window 70~110℃. Example 3 (High heat shrinkage + anti-fouling heat sealing)
[0052] Structure: Same as Example 1, but the heat-sealing layer is changed to PBS (melting point 115℃) + 1.5% PCL-PEG block copolymer; biaxial stretching ratio 6×6, heat setting temperature 70℃.
[0053] Performance: Heat shrinkage rate 58% / 55%; heat seal strength (100℃, 0.3MPa, 1s) = 15 N / 15mm; OTR = 42, WVTR = 30, light transmittance 86%, haze 7%. Comparative Example 1 (without nano-VCI)
[0054] Same formulation as Example 1, but without the addition of nano-VCI barrier agent. Performance: OTR=45, WVTR=32, CO2TR=160; light transmittance 88%, haze 6%; heat shrinkage 14%; heat seal strength 13.8 N / 15mm. This indicates that nano-VCI reduces OTR by 38% and WVTR by 22%.
[0055] When the same formulation as in Examples 2 and 3 was used but without the addition of nano-VCI barrier agent, OTR, WVTR, etc. were also significantly reduced, which was comparable to the performance change range of Comparative Example 1. Comparative Example 2 (Design without heat seal layer)
[0056] The core material of Example 1 was used as the heat-sealing layer (i.e., without a dedicated low-melting-point layer). The heat-sealing initiation temperature required was 135°C, and the heat-sealing window was only 105~135°C (ΔT=30°C), but the strength in the low-temperature range (<120°C) was <5 N / 15mm, which did not meet the requirements for automated packaging. Comparative Example 3 (Heat seal layer without antifouling additives)
[0057] Compared to Example 1, no PEO was added to the heat seal layer. Under oily conditions, the heat seal strength decreased to 5.6 N / 15 mm (compared to 11.2 N / 15 mm in Example 1), demonstrating the necessity of antifouling additives. Comparative Example 4 (Pure PBAT monolayer membrane)
[0058] It is unobstructed, non-transparent, has low heat shrinkage, and moderate heat-sealing performance.
[0059] Table 1. Partial properties of the thin films obtained in each embodiment and comparative example.
[0060] Table 2 Mechanical properties of the films obtained in each embodiment and comparative example
[0061] Those skilled in the art will readily understand that the above description is only a part of the embodiments of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A high-barrier multilayer co-extruded biodegradable film that combines transparency and heat shrinkage, characterized in that, The multilayer co-extruded biodegradable film comprises a heat-sealing layer, a first barrier core layer, a second barrier core layer, and an outer surface layer; wherein, the heat-sealing layer is a low-melting-point biodegradable polyester layer, selected from one or more of polybutylene adipate terephthalate (PBAT), polybutylene succinate (PBS), and polycaprolactone (PCL); the first and second barrier core layers are each independently selected from one or more of polyvinyl alcohol (PVA), polypropylene carbonate (PPC), polylactic acid (PLA), and PBAT, and contain organic-inorganic hybrid nanofillers and nano-VCI barrier agents; the outer surface layer is a heat-resistant, anti-adhesion biodegradable layer, selected from one or more of PLA, PVA, or PLA / PHA.
2. The high-barrier multilayer co-extruded biodegradable film with both transparency and heat shrinkage as described in claim 1, characterized in that, The heat-sealing layer also contains an anti-fouling heat-sealing agent, which is polyethylene oxide (PEO), polycaprolactone-polyethylene glycol (PCL-PEG) block copolymer, or fatty acid amide; preferably, the amount of the anti-fouling heat-sealing agent added is 0.1% to 2% of the mass of the heat-sealing layer; preferably, the melting point of the heat-sealing layer is 20 to 60°C lower than that of the core layer and the outer layer.
3. The high-barrier multilayer co-extruded biodegradable film with both transparency and heat shrinkage as described in claim 1, characterized in that, The organic-inorganic hybrid nanofiller is one or more of nano-montmorillonite, nano-silica, and nano-kaolinite; preferably, the organic-inorganic hybrid nanofiller is pretreated with a silane coupling agent; preferably, the surface pretreatment method is mixing at 95-105℃ for 10-20 min; preferably, the particle size of the organic-inorganic hybrid nanofiller is 30~500 nm; preferably, the amount of organic-inorganic hybrid nanofiller added is 1%~15% of the total mass of the film.
4. The high-barrier multilayer co-extruded biodegradable film with both transparency and heat shrinkage as described in claim 1, characterized in that, The nano-VCI barrier is a type of functional material with nanoscale properties that can actively adsorb or chemically bind small molecule gases; preferably, the nano-VCI barrier is selected from one or more of nano-zeolite, nano-metal-organic framework materials, nano-activated carbon, and nano-molecular sieves; preferably, the nano-VCI barrier is pre-modified with a surface oleophilic agent, and the modifier is selected from silane coupling agents, titanate coupling agents, or oleic acid; preferably, the particle size of the VCI barrier is 20~200 nm; preferably, the amount of VCI barrier added is 0.5%~10% of the total mass of the film, more preferably 1%~5%.
5. The high-barrier multilayer co-extruded biodegradable film with both transparency and heat shrinkage as described in claim 1, characterized in that, The total thickness of the film is 20-200 μm, wherein the heat-sealing layer accounts for 10%-25% of the thickness, the total thickness of the first barrier core layer and the second barrier core layer accounts for 50%-70%, and the outer layer accounts for 15%-30% of the thickness; preferably, the first barrier core layer is the main barrier layer, with a thickness accounting for 25%-40% of the total film thickness; preferably, the first barrier core layer is PVA / PLA or PPC / PLA, with 5%-15% nano-montmorillonite and 0.5%-5% nano-VCI barrier agent added; preferably, the second barrier core layer is an auxiliary barrier layer, with a thickness accounting for 25%-40% of the total film thickness; preferably, the second barrier core layer is PBAT / PLA resin, with nano-silica and nano-VCI barrier agent added.
6. The high-barrier multilayer co-extruded biodegradable film with both transparency and heat shrinkage as described in claim 1, characterized in that, The thickness of the heat-sealing layer is 5~30 μm; preferably, an anti-blocking agent is added to the outer surface layer; preferably, the anti-blocking agent is 0.1%~0.5% nano-silica.
7. The method for preparing a high-barrier multilayer co-extruded biodegradable film with both transparency and heat shrinkage as described in any one of claims 1-6, characterized in that, The method includes the following steps: (1) Raw material pretreatment: each layer of resin is dried, and the nanofiller and nano VCI barrier are respectively pretreated by coupling agent surface treatment; (2) Multi-layer co-extrusion blow molding: The materials of each layer are premixed according to the formula and fed into the extruder of the multi-layer co-extrusion blow molding unit. The materials of each layer are plasticized and melted at 150~230℃ and then extruded through the multi-layer die head to form a molten preform. (3) The preform is inflated, cooled, and drawn to form a primary film; (4) Biaxial stretching: After the blown film bubble is cooled, it is reheated to the stretching temperature and stretched longitudinally and laterally. Then it is heat-treated in the heat setting zone and finally wound up.
8. The method for preparing a high-barrier multilayer co-extruded biodegradable film with both transparency and heat shrinkage as described in claim 7, characterized in that, The film is heat-sealed at a temperature of 80~120℃, a pressure of 0.2~0.5 MPa, and a time of 0.5~2 seconds, with a heat-sealing strength ≥12 N / 15mm, and no stringing or sticking to the roller at the heat-sealed area; preferably, a five-layer co-extrusion blow molding unit is used in the multi-layer co-extrusion blow molding; preferably, the extrusion temperature of each layer is: heat-sealing layer 150~170℃, core layer 180~210℃, outer layer 190~220℃, and die head temperature 190℃.
9. The method for preparing a high-barrier multilayer co-extruded biodegradable film with both transparency and heat shrinkage as described in claim 7, characterized in that, The melting point of the heat-sealing layer material is 20-60°C lower than that of the outer and core layer materials, and the heat-sealing initiation temperature is 80-100°C. After biaxial stretching, the crystallinity of the heat-sealing layer is controlled at 15%-35% to obtain a wide heat-sealing window. The heat-setting temperature should be 10-20°C lower than the melting point of the heat-sealing layer to obtain a rapid heat-sealing response.
10. A heat-shrinkable packaging bag or a food preservation packaging bag, characterized in that, The heat-shrinkable packaging bag or food preservation packaging bag is made from a high-barrier multilayer co-extruded biodegradable film with both transparency and heat shrinkability as described in any one of claims 1-6, through heat sealing or heat shrink molding.